Pengembangan Media Tajwid Interaktif Berbasis Augmented Reality untuk Meningkatkan Visualisasi Hukum Bacaan di Madrasah Aliyah - Andik Prakasa Hadi; Rudjiono Rudjiono (Pusat Riset dan Inovasi Nasional, 2025)
This study explores the development and implementation of an Augmented Reality (AR)-based learning medium to enhance students’ understanding of tajwid at Madrasah Aliyah. The background of this research stems from the limited effectiveness of conventional teaching methods and the relatively low interest of students in learning tajwid. AR-based learning was chosen because it provides a more interactive and contextualized learning experience that actively engages learners. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants were Madrasah Aliyah students selected as the experimental group. The findings reveal that the AR learning medium significantly improves students’ comprehension of tajwid rules compared to traditional learning approaches. Moreover, students reported high levels of satisfaction, noting that the media was engaging, user-friendly, and capable of visualizing abstract tajwid rules in a clear and accessible manner. In conclusion, integrating AR technology into Islamic education, particularly tajwid learning, holds great potential to improve learning quality while fostering students’ motivation to explore the subject more deeply.